Study of thermodynamic water properties and moisture sorption hysteresis of mango skin - Souza, Silvio José Ferreira de [UNESP]; Alves, Aline Inácio; Vieira, Érica Nascif Rufino; Vieira, José Antônio Gomez [unesp]; Ramos, Afonso Mota; Telis-Romero, Javier [UNESP] (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2015)
The equilibrium moisture content for adsorption and desorption isotherms of mango skin was determined using the static gravimetric method at temperatures of 20, 26, 33, 38 and 44 oC in the 0.056 to 0.873 water activity range. Both sorption curves show a decrease in equilibrium moisture content as the temperature increasing. The hysteresis effect was observed at constant water activity. The Guggenheim, Anderson, and de Boer (GAB) model presented the best fitting accuracy among a group of models and was used to determine the thermodynamic properties of water sorption. Integral enthalpy and integral entropy areas showed inverted values for the adsorption and desorption isotherms over the wide range of water activity studied. These values confirm, in energetic terms, the difference between adsorption and desorption isotherms observed in the hysteresis phenomenon. Finally, the Gibbs free energy revealed that the sorption process was spontaneous for both sorption isotherms.
Keywords: Agricultural waste; Gravimetric method; Integral properties; Modelling; Water content